Feeling our Way: A Trioethnography on Critical Affective Literacy for Applied Linguistics - Uddin Ahmed, Anwar; Morgan, Brian; Maciel, Ruberval Franco (Calidoscópio, 2022)
This paper argues that attention to affect/emotion be given greater prominence in applied linguistics following a theoretical and pedagogical framework delineated as critical affective literacy (CAL) by Anwaruddin (2016). Following a brief description of key CAL principles, the authors explore the potency of affect and emotionality of texts by way of duo/trioethnography (Norris & Sawyer, 2012, 2017), a research methodology particularly relevant for exploring affective/emotional dimensions of language in educational domains (e.g., English for Academic Purposes, Language Teacher Education, English for Medical Purposes) and as part of broader socio-political deliberation. The authors detail specific features of duoethnographic research methodology (e.g., participant transparency and juxtaposition, epistemological and ideological risk-taking) that contribute to CAL principles and aspirations. In the final sections of the paper, the authors identify several implications of their trioethnography for the development of CAL in applied linguistics followed by brief descriptions of curricular and pedagogical innovation where affect/emotion has been integral to the pedagogical and literacy strategies described. Key Words: affect; emotion; critical affective literacy; duoethnography; democratic pedagogies.